xy and yx are identical so you have 2xy = 545 ie xy = 272.5. Possible answers 5 and 54.5, 10.9 and 25 etc
The problem to solve is: xy+x+3y+3 Multiply y and x Multiply the y and x Multiply y and x The y just gets copied along. The x just gets copied along. The answer is yx yx x*y evaluates to yx x*y+x evaluates to yx+x Multiply y and 3 Multiply y and 1 The y just gets copied along. The answer is y y 3*y evaluates to 3y The answer is yx+x+3y x*y+x+3*y evaluates to yx+x+3y The answer is yx+x+3y+3 x*y+x+3*y+3 evaluates to yx+x+3y+3 ---- The final answer isyx+x+3y+3----
xy + y = z xy = z - y (xy)/y = (z - y)/y x = (z - y)/y
This gives us the equations: n = xy = yx x != y (Note that for this example, the != stands for not equal to similar to some programming languages.) xy always equals yx due to the communtative property of multiplication. So there are actually an infinite number of answers. Some are given below: 6 = (2)(3) = (3)(2), 2 != 3 12 = (3)(4) = (4)(3), 3 != 4
x+xy=8 xy=-x+8 y=-1+8/x
If x+y = 3 and y times x = 2 then y = 1.
xy over yx can be simplified to 1. 2x over 2y can be simplified to x over y. So the final step would be to simplify 1 divided by x over y, which would just be 1 multiplied by y over x. Answer: y/x (y over x)
k = x y x = k/y
"xy" refers to the product of "x" and "y". Just substitute the variables for numbers, and do the multiplication.
If Y = 0 then there is no value of X such that XY = 1.